Association of ADRB2 gene polymorphism with dilated cardiomyopathy - Svetlana Y. Nikulina (Concilium Medicum, 2021)
Aim. To study the association of the rs1042713 polymorphism of the ADRB2 gene with cardiomyopathies of various origins.